New MAX Phase Superconductor Ti2GeC: A First-principles Study (Journal of Scientific Research, 2013)
This is the first DFT-based first-principles prediction of the detailed optical and thermodynamic properties, including Vickers hardness and Fermi surface of 211 MAX phase Ti2GeC for which superconductivity (Tc~ 9.5 K) was reported very recently. The calculated structural properties are in excellent agreement with experiments. Our results on elastic parameters indicate a slight elastic anisotropy and brittleness of the compound. The chemical bonding is seen to be a combination of covalent, ionic and metallic nature. The rather stronger covalent bonding is responsible for its high Vickers hardness of 11.6 GPa. The investigated Fermi surface is formed mainly by the low-dispersive bands, which should be responsible for the presence of superconductivity in Ti2GeC. All the optical properties are evaluated and analyzed for two different polarization directions of incident photon. The temperature and pressure dependence of primitive cell volume, thermal expansion coefficient, specific heats, bulk modulus, and Debye temperature of Ti2GeC are derived from the quasi-harmonic Debye model with phononic effect and the various implications are discussed in details.  Keywords: First-principles calculation; Vickers hardness; Optical properties; Thermodynamic properties. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.16604 J. Sci. Res. 6 (1), 11-27 (2014)